HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MENGENAI COVID-19 TERHADAP TINGKAT KEPATUHAN MELAKUKAN PROTOKOL KESEHATAN PADA PASIEN DIABETES MELITUS TIPE 2 DI RSU KABUPATEN TANGERANG - Rajwa Zahra Mardhiyyah, (2022)
Diabetes Mellitus is a chronic disease characterized by an increase in blood sugar from normal limits. According to data from the Ministry of Health, Indonesia occupies the seventh position in the highest number of diabetics worldwide in 2019. The COVID-19 mortality rate is high in DM patients, so awareness is needed in terms of preventing transmission through health protocols. Factors that can affect individual compliance are the level of knowledge and attitudes. The purpose of this study was to determine the relationship between the level of knowledge and attitudes regarding COVID-19 on adherence to implementing health protocols in type II DM patients at the Tangerang Regency General Hospital. This type of research is quantitative with an observational analytical research design and a Cross Sectional approach. Using Consecutive Sampling with a sample size of 68 respondents. The instrument used is a questionnaire. Data analysis used univariate and bivariate analysis. The results of the univariate analysis of respondents had a high level of knowledge as many as 43 people (63.2%), a good attitude as many as 52 people (76.5%) and included in the category of obedient to health protocols as many as 44 people (64.7%). The results of the bivariate analysis showed that the level of knowledge p value=0.722 and attitude p value=0.000 with OR=16.152 (3.90-66.880). It can be concluded that the level of knowledge does not have a significant relationship with health protocol compliance and on attitude there is a significant relationship with health protocol compliance.